DNA MISMATCH REPAIR PROTEINS EXPRESSION STATUS IN PATIENTS WITH COLORECTAL ADENOCARCINOMA AT THANH HOA ONCOLOGY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the MMR protein expression status and identify factors associated with MMR deficiency in patients with colorectal adenocarcinoma.Subjects and methods: A descriptive cross-sectional study was conducted on 208 patients with colorectal adenocarcinoma treated at Thanh Hoa Oncology Hospital between January 2024 and May 2026.Results: The prevalence of dMMR was 12.5%. The most common pattern of MMR protein loss was concurrent loss of MLH1-PMS2 (42.3%), followed by concurrent loss of MSH2-MSH6 (30.8%). The prevalence of dMMR was four times higher in patients aged < 50 years than in those aged 50-70 years and 6.3 times higher than in patients aged > 70 years. Tumors measuring ≥ 5 cm had a 4.7-fold higher prevalence of dMMR than tumors < 5 cm. Poorly differentiated tumors exhibited a six-fold higher prevalence of dMMR than moderately differentiated tumors, while mucinous adenocarcinomas showed a three-fold higher prevalence than conventional adenocarcinomas. dMMR was also more frequently observed in tumors located in the transverse and right colon than in the left colon and rectum.Conclusion: Loss of MMR protein expression is more likely to occur in younger patients and is associated with larger tumor size, mucinous histology, and poorly differentiated tumors.
Keywords: DNA mismatch repair proteins, microsatellite instability, colorectal cancer.